De skjulte erfaringsstrukturer i Karl Barths sene teologi - Põder, Christine Svinth-Værge (Dansk Teologisk Tidsskrift, 2008)
Karl Barth has regularly been criticized for a concept of revelation which seems to leave no space for human subjectivity, while insisting on the exclusively objective character of the divine act. The aim of this article, “The hidden experiential structures of Karl Barth’s late thought”, is to examine the structures of perception in Church Dogmatics. The article proposes that Barth’s objectivist approach to divine action is a feature of a particular strategy: He is doing justice to religious perception, not by treating it as a subject in its own right, but by employing its perspective methodologically when circumscribing the imperceptible encounter between God and humans in dogmatic and objectivist terms. Elaborating this thesis the article points to the significance of actualist structures in Barth’s theology by analyzing the relations between prayer and praise, human activity and perception.